Health claims and product endorsements on child-oriented beverages in Guatemala. Issue 3 (16th November 2017) - Perry, Andrew; Chacon, Violeta; Barnoya, Joaquin
Abstract: Objective: We sought to describe front-of-package marketing strategies and nutritional quality of child-oriented beverages in Guatemala. Design: We purchased all child-oriented ready-to-drink fruit drinks, milks and carbonated beverages in three convenience stores and one supermarket in Guatemala City. Front-of-package marketing was defined as the presence of spokes-characters, cartoons, celebrities, or health-related images, words, claims or endorsements on beverage packaging. We used the UK Nutrition Profiling Model (NPM) to classify beverages as healthy or less healthy. Setting: Guatemala City, Guatemala. Results: We purchased eighty-nine beverages; most were fruit drinks ( n 52, 58 %), milk (15, 17 %), carbonated beverages (5, 17 %), rice/soya products (5, 6·0 %), water (1, 1 %) and energy drinks (1, 1 %). Two-thirds (57, 64 %) had health claims. Of those with a nutrition facts label (85, 96 %), nearly all (76, 89 %) were classified as less healthy. No association between the presence of health claims and NPM score ( P =0·26) was found. Eight beverages had health-related endorsements. However, only one beverage was classified as healthy. Conclusions: In this sample of beverages in Guatemala City, health claims and health-related endorsements are used to promote beverages with poor nutritional quality. Our data support evidence-based policies to regulate the use of front-of-package health claims and endorsements based on nutritional quality.